2021
DOI: 10.3390/ma14154165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Erosivity of High-Pressure Pulsating Water Jets Produced in the Self-Excited Drill Head

Abstract: The dynamic impact of a water jet with a periodically changing structure can be used in various industries. The paper presents a design solution for a self-excited pulse head. This head can be used in mining for drilling holes and breaking rocks. The design of the head was developed based on computer simulations, which made it possible to learn the mechanism of impulse shaping inside the head. Tests of the water jet produced in the self-excited pulsation head showed the occurrence of periodic changes in its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Based on the obtained results, it was found that for the head model with two side holes, the inlet of medium occurred when the diameter of the inlet nozzle was smaller than the diameter of the outlet nozzle (d1< d3) [31]. The greatest value of inlet mass velocity through the side holes was obtained for d3=1.2 mm and d1=0.6 mm.…”
Section: Simulation Studies Of a Self-excited Pulse Head With Differe...mentioning
confidence: 91%
See 2 more Smart Citations
“…Based on the obtained results, it was found that for the head model with two side holes, the inlet of medium occurred when the diameter of the inlet nozzle was smaller than the diameter of the outlet nozzle (d1< d3) [31]. The greatest value of inlet mass velocity through the side holes was obtained for d3=1.2 mm and d1=0.6 mm.…”
Section: Simulation Studies Of a Self-excited Pulse Head With Differe...mentioning
confidence: 91%
“…The solution was examined in terms of the influence of the number of holes on the surface cleaning process. The principle concerning the location of the side holes perpendicular to the chamber was used in all such heads, regardless of their application [30,31,32]. The simulation tests were carried out for the same range of diameter variation (0.6 ÷ 1.2 mm) of both types of nozzles: inlet d1 and outlet d3 at a constant pressure of 15 MPa and maintaining the unchanged values of the other dimensional parameters of the self-excited pulse head.…”
Section: Simulation Studies Of a Cutting Head Model Designed For The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of loose abrasive particles in the cutting zone, where substantial forces are present, can lead to various issues. This phenomenon finds application in water jet machining, where loose abrasive particles are propelled into the medium at high pressure, or occasionally, the medium's pressure alone is adequate to induce erosive effects on the surface [49,50]. Partially liberated abrasive grain parts from the bond can also be observed, with fragmented grain residues remaining attached to the carrier (Figure 17h).…”
Section: Surface Analysis Of the Worn Abrasive Toolmentioning
confidence: 99%
“…Another way of pulsing jet generation, applying self-excited oscillations in the nozzle, has attracted waterjet researchers for years [ 4 , 5 , 6 , 7 ] but it still remains in the experimental phase although it should be more energy-saving and environmentally friendly. Quite recently, a brand new promising study introducing a self-excited pulse waterjet head applicable in mining for drilling holes and breaking rock was published [ 8 ]. The presented research is focused on the waterjet stability improvement in the near field and support of jet pulsation in the far-field which represents the operation zone of the device.…”
Section: Introductionmentioning
confidence: 99%